Pola Komunikasi Pengguna Media Sosial dalam Perilaku People Pleasing terhadap Ekspektasi Sosial - Anggraeni, Apriyani; Loisa, Riris; Irena, Lydia (Koneksi, 2026)
The development of technology and social media encourages users to adjust their communication patterns to gain social acceptance, which in turn gives rise to the phenomenon of people pleasing in the digital space. This study examines the communication patterns of Instagram users in meeting social expectations, particularly through the phenomenon of people-pleasing, from the perspective of Erving Goffman's dramaturgy. Social media, especially Instagram, is used by users to project a more perfect self-image as part of impression management, while their true identities are more often displayed in private spaces. This study uses a qualitative approach with a phenomenological method through in-depth interviews, observation of informants' Instagram accounts, and documentation. The results show that pressure from the social environment influences how a person communicates, selects content, edits posts, and chooses language to gain recognition from others. The phenomenon of people-pleasing emerges as a way to maintain a positive image and elicit responses from the audience through various channels such as stories, comments, and direct messages. The research findings also indicate that users utilize the DM feature as a place for more authentic interactions, while public posts become a "front stage" for presenting an ideal version of themselves. This research helps understand how social expectations shape communication in the digital world and emphasizes the importance of honest and balanced interactions. Perkembangan teknologi dan media sosial mendorong pengguna untuk menyesuaikan pola komunikasinya demi memperoleh penerimaan sosial, yang kemudian memunculkan fenomena people pleasing di ruang digital. Penelitian ini membahas pola komunikasi pengguna Instagram dalam berkomunikasi untuk memenuhi harapan sosial, khususnya melalui fenomena people pleasing, dilihat dari sudut pandang dramaturgi Erving Goffman. Media sosial, terutama Instagram, digunakan oleh pengguna untuk menunjukkan gambaran diri yang lebih sempurna sebagai bagian dari pengelolaan kesan, sementara identitas sebenarnya lebih sering ditampilkan di area pribadi. Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologi melalui wawancara mendalam, pengamatan akun Instagram informan, dan dokumentasi. Hasil penelitian menunjukkan bahwa tekanan dari lingkungan sosial memengaruhi cara seseorang berkomunikasi, memilih konten, mengedit unggahan, serta memilih bahasa untuk memperoleh pengakuan dari orang lain. Fenomena people pleasing muncul sebagai cara untuk mempertahankan citra positif dan memancing respons dari audiens melalui berbagai saluran seperti story, komentar, dan pesan langsung. Temuan penelitian juga menunjukkan bahwa pengguna memanfaatkan fitur DM sebagai tempat interaksi yang lebih autentik, sementara unggahan publik menjadi tempat "panggung depan" untuk menampilkan versi diri yang ideal. Penelitian ini membantu memahami bagaimana harapan sosial membentuk komunikasi di dunia digital dan menekankan pentingnya interaksi yang jujur serta seimbang.